Cardiovascular risk factors as potential biomarkers of length of hospital stay and rehospitalization in mood disorders – a retrospective study - Eva Kathrin Lamadé; Bruno Pedraz-Petrozzi; Bernhard Schaupp; Nicole Özer; Bertram Krumm; Michaela Coenen; Sibylle Häfner; Maria Gilles; Andreas Meyer-Lindenberg; Michael Deuschle (Biomarkers in Neuropsychiatry)
Objective: Cardiovascular diseases are often comorbid with mood disorders, increasing the burden on patients. Few studies explore the role of cardiovascular disease on psychiatric inpatient stays. This retrospective study investigated the association of cardiovascular risk factors during an index stay on psychiatric length of stays and rehospitalization in the subsequent 10 years in patients with mood disorders. Methods: Patients with a first inpatient stay in two German psychiatric hospitals, diagnosed with F31 (bipolar affective disorder), F32 (depressive episode) or F33 (recurrent depressive disorder) were investigated (n=930). The association of hypertension, hypercholesterolemia, and type 2 diabetes mellitus at the index stay with total length of stays, average length of stay and rehospitalization in the next 10 years was investigated in bivariate, and multivariate regression analyses, adjusting for sex, age, BMI, smoking, taking antidepressants and antipsychotics. Results: Patients averaged 99.27 (± 134.94) inpatient days within 10 years, patients with hypertension 138.09 (± 162.85) days. Controlling for confounders, hypertension associated with longer total length of stays (β=0.105, p=0.044), hypertension (β=0.146, p=0.004), hypercholesterolemia (β=0.104, p=0.034) and diabetes (β=0.103, p=0.015) linked to more rehospitalizations and not having hypercholesterolemia (β=0.101, p=0.041) related to longer average stays. Sex mediated the relationship between hypercholesterolemia and both rehospitalization (F=11.60, p<0.001) and total length of stays (F=7.21, p=0.007), with males with hypercholesterolemia showing more rehospitalization and longer total length of stays than females. Conclusion: Cardiovascular risk factors were associated with duration and frequency of psychiatric inpatient stays in patients with mood disorders. Cardiovascular risk factors as potential predictive biomarkers for the course of disease of mood disorders should be monitored and managed.